Bridging The Financial Reporting Gap In MSMES: The Role of SIAPIK Applications, Success Factors, And Barriers - Nisa, Fadhila Auliya; Putra, Yuniarti Hidayah Suyoso (E-Jurnal Akuntansi; Vol 35 No 7 (2025), 2025)
This study aims to examine and evaluate the implementation of the SIAPIK application, launched by Bank Indonesia, in assisting MSMEs in Malang City, East Java, to prepare financial statements. The SIAPIK application is accounting software designed to make it easier for MSMEs to record financial transactions and prepare financial reports in accordance with MSME Financial Accounting Standards. The subjects of this study include MSMEs using the SIAPIK application. There were 6 informants who were used as research samples. The results show that the SIAPIK application has been widely used by MSMEs in Malang City, East Java. Factors contributing to its successful implementation include ease of access, data security, high-quality information, good service, user satisfaction, no fees, convenience, and support from the government and community. Utilization of the SIAPIK application has also been shown to improve MSME financial reports. Nonetheless, there are still challenges faced, such as limited ongoing support, educational background impacting digital literacy, inadequate IT infrastructure and lack of detailed features.  This study suggests creating a mentoring program for MSME operators and making better system improvements to meet the current operational needs of MSMEs.perational needs of MSMEs. Keywords: MSMEs; SIAPIK Applications; Quality of Financial Statements; Success Factors; Inhibiting Factors